Innovation of easy learning basic pattern for beginners as teaching materials in field of sewing - Muhamil, Shariffah Eqlima; Hanapi, Zaliza; Subri, Ummu Sakinah; Mohamed, Suriani; Tze Kiong, Tee (Hrmars, 2021)
This study aims to develop a teaching tool called Easy Learning Basic Pattern for Beginners to solve problems that arise when students design patterns. The selected sample involved Form 4 students who took the Household Science subject to determine the effectiveness of this teaching aid innovation. A questionnaire containing 32 items was distributed to the respondents and analysed descriptively using the Statistical Package for Social Sciences software version 23. The study found that students’ perceptions towards the proposed teaching aid are high in terms of understanding and interest in sewing. The results can help students to understand the steps to design patterns correctly and serves as one of the teaching aids that can be utilised by teachers in teaching sewing.